Preaching During the COVID-19 Pandemic in South Africa: A Grounded Theoretical Exploration - Steyn, Marileen; Wepener, Cas; Pieterse, Hennie (International Journal of Homiletics, 2020)
Churches have been prompted to rethink the format of preaching and the content of sermons since the outbreak of the COVID-19 pandemic and the consequent restrictions on church gatherings. What does preaching look like, or what may it look like in times of crisis? These questions arose, specifically considering the content of sermons in the week before and after the national lockdown was announced in South Africa. Using Grounded Theory, the content of sermons delivered during this period was examined in order to identify an emerging theory regarding the homiletical content. From these findings, a homiletic praxis theory is formulated for preaching in times like these. The tension between proximity and distance that is experienced by hearers and proclaimed by preachers is explored. Habits of faith and discernment emerge as core concepts in mitigating this tension and in navigating the thin spaces that are created by liminal times such as these.